"We didn't tell everybody because everybody didn't need to know": an examination of parental disability-disclosure of Spina Bifida. Issue 9 (21st October 2018) - Copeland, Kristopher; Lasater, BreeAnna L.
Abstract: This qualitative study sheds light on the process that parents go through as they learn of a spina bifida diagnosis and the communication strategies that are used to discuss an expected disability diagnosis with others. Interviews with 30 participants discovered that there were immediate disclosures made with family and close friends. Additionally, circumstantial disclosures took place when returning to routine behaviors. Participants described five distinctive criteria that developed a privacy boundary: self-blame, grief, helping others cope, maintaining privacy of child, and stigma. Implications for parents, medical professionals, and communication scholars are discussed.